Transforming Islamic Moral Values into an Anti-Bullying School Culture: An Akhlakul Karimah-Based Conceptual Model for Indonesian Madrasahs - Nur Aliyah; Abdul Aziz (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
Bullying remains a persistent challenge in Indonesian madrasahs, requiring preventive approaches that integrate moral education with school culture. This study aims to examine how Islamic Religious Education teachers transform akhlakul karimah values into a sustainable anti-bullying school culture and to develop an empirically grounded conceptual model. A qualitative case study was conducted through interviews, observations, and document analysis involving school leaders, Islamic Religious Education teachers, and students in an Indonesian madrasah. Data were analyzed using thematic analysis with triangulation to ensure credibility. The findings reveal that bullying prevention is more effective when teachers function as transformational role models who internalize compassion, brotherhood, respect, tolerance, and social responsibility through learning, moral reflection, habituation, peer support, and institutional reinforcement. The study proposes an Akhlakul Karimah-Based Anti-Bullying School Culture Model comprising four interconnected components: value internalization, teacher role modelling, moral habituation, and institutional reinforcement. This model extends existing bullying prevention frameworks by integrating Islamic moral pedagogy with school culture theory and offers practical guidance for educators, school leaders, and policymakers seeking sustainable character-based bullying prevention in Islamic educational settings and future comparative research.